Control of crystallite and particle size in the synthesis of layered double hydroxides: macromolecular insights and a complementary modeling tool - Galvão, Tiago L. P.
Zinc–aluminum layered double hydroxides with nitrate intercalated (Zn(n)Al–NO3, n = Zn/Al) is an intermediate material for the intercalation of different functional molecules used in a wide range of industrial applications. The synthesis of Zn(2)Al–NO3 was investigated considering the time and temperature of hydrothermal treatment. By examining the crystallite size in two different directions, hydrodynamic particle size, morphology, crystal structure and chemical species in solution, it was possible to understand the crystallization and dissolution processes involved in the mechanisms of crystallite and particle growth. In addition, hydrogeochemical modeling rendered insights on the speciation of different metal cations in solution. Therefore, this tool can be a promising solution to model and optimize the synthesis of layered double hydroxide-based materials for industrial applications.